PA.47 A Novel System of Maternity Triage in the Obstetric Assessment Unit. (9th June 2014) - Perry, H; Lindley, CM; Northover, E; Connor, JI; Parasuraman, R
Abstract : Background: The number of women attending the obstetric assessment unit (OAU) for unscheduled antenatal care is unpredictable often with long delays in initiating treatment in these high risk women. Aims: To design and pilot a triage system to prioritise patient care and aid patient flow through a busy OAU thereby creating a system by which the most urgent cases receive timely care aiming to reduce poor outcomes due to delays in treatment. The aim is to perform a basic assessment within 15 min15 minutes of arrival, Methods: A robust clinical assessment was carried out for each woman on arrival by a senior midwife using a triage assessment sheet. The women were then triaged according to clinical need based on a 'Traffic light system' devised locally based on Emergency Department protocols. Results: There were 38 women seen in the period of the pilot. The majority of women (58%) were in the 'amber' category with 5% in the 'red'. 55% of women were triaged within 15 and 79% within 30 min. Women were classified correctly in 90% of cases. 66% of women were self-referrals, 18% from community midwives and 5.3% from GPs. Discussion: The triage system will ensure that women are given advice, care or transferred to the clinical area that is most suitable to their individual needs. The pilot study has identified delays still occurring in the initial assessment and on-going work will aim to identify and address the cause of these delays.